2016
DOI: 10.1111/jace.14618
|View full text |Cite
|
Sign up to set email alerts
|

Re‐entrant relaxor behavior in BaTiO3‐Bi(Zn2/3Nb1/3)O3 ceramics

Abstract: The (1−x)BaTiO3−xBi(Zn2/3Nb1/3)O3 (x=0.10‐0.25) ceramics were fabricated via solid‐state reactions. Temperature‐dependent polarization measurement reveals that with the temperature lowering, the remnant polarization increases till a maximum value before it decreases, showing a reentrant phenomenon. Absence of apparent switching current peaks in the current density as a function of electric field should indicate the lack of a ferroelectric transition, which is further verified by the consistent macroscopic phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Interestingly, an anomalous peak was found at 348 K in Figure , which is also consistent with the inherent re‐entrant temperature determined from the imaginary part of the dielectric constant (Figure B). Consequently, this anomalous peak should confirm that with decreasing temperature, the PNRs (formed by clustering of B‐site ions) in the system enters a more disordered state . Meanwhile, the broad Raman peak is related to microscopic chemical heterogeneity due to the difference in ionic size, valence, and electronegativity of B‐site ions .…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Interestingly, an anomalous peak was found at 348 K in Figure , which is also consistent with the inherent re‐entrant temperature determined from the imaginary part of the dielectric constant (Figure B). Consequently, this anomalous peak should confirm that with decreasing temperature, the PNRs (formed by clustering of B‐site ions) in the system enters a more disordered state . Meanwhile, the broad Raman peak is related to microscopic chemical heterogeneity due to the difference in ionic size, valence, and electronegativity of B‐site ions .…”
Section: Resultsmentioning
confidence: 81%
“…1,2 It is reported that a re-entrant relaxor behavior is presented in BaTiO 3 -BiScO 3 , BaTiO 3 -Bi(Zn 2/3 Nb 1/3 )O 3 , and (K 0.5 Na 0.5 ) NbO 3 -(Na 1/2 Bi 1/2 )TiO 3 . [3][4][5] Meanwhile, the similar behaviors have been reported in Pb/Bi-based perovskites, such as (Ba 0.925 Bi 0.05 )(Ti 1-x/100 Sn x/100 )O 3 and Pb 0.76 Ca 0.24 TiO 3.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Following such initial success, solid solutions with more complex Me substitutions on the B site were also explored for potential improvements in dielectric properties. Examples include BaTiO 3 ‐Bi(Zn 1/2 Ti 1/2 )O 3 , BaTiO 3 ‐Bi(Zn 2/3 Nb 1/3 )O 3 , BaTiO 3 ‐Bi(Mg 2/3 Nb 1/3 )O 3 , and BaTiO 3 ‐Bi(Zn 1/2 Ti 1/2 )O 3 ‐BiScO 3 . The incorporation of additional Me ions is presumed to enhance the net atomic displacements at the B site, thereby giving rise to higher electrical dipole moments and therefore larger k .…”
Section: Introductionmentioning
confidence: 99%
“…Following such initial success, solid solutions with more complex Me substitutions on the B site were also explored for potential improvements in dielectric properties. Examples include BaTiO 3 [7][8][9][10][11][12][13] The incorporation of additional Me ions is presumed to enhance the net atomic displacements at the B site, thereby giving rise to higher electrical dipole moments and therefore larger k. While some promising trends are indeed observed for the above listed dielectric ceramics, they nevertheless face several shortcomings. The frequency-independent response of (1-x) BaTiO 3 -xBiMeO 3 dielectrics are observed only above 150°C.…”
mentioning
confidence: 99%